The effect of leguminous cover crops and cowpea planted as border rows on maize ear borers with special reference to Mussidia nigrivenella Ragonot (Lepidoptera: Pyralidae) - Agboka, K.; Schulthess, F.; Tounou, A.K.; Tamò, Manuele; Vidal, S. (Elsevier, 2013)
In southern Benin, the use of cover crops to improve and maintain soil fertility is on the increase. The present study investigated the effect of two leguminous cover crops, Canavalia ensiformis (L.) DC and Sesbania rostrata Brem. & Oberm., planted at different dates before maize (Zea mays (L.)), and cowpea (Vigna unguiculata L.) planted as border rows on infestations of maize by the pyralid Mussidia nigrivenella Ragonot and of other cob-boring lepidopteran pests. In both trials, M. nigrivenella densities at harvest tended to be higher in the maize alone than the legume treatments, but the effect depended on the timing of planting of the cover crop in relation to that of maize. There were no discernible trends for other borers such as the noctuid Sesamia calamistis Hampson, the pyralid Eldana saccharina Walker, and the tortricid Thaumatotibia leucotreta Meyrick. Furthermore, M. nigrivenella pest loads were considerably higher on C. ensiformis than maize, indicating that the presence of alternative host plant species in the vicinity of maize fields did not increase M. nigrivenella attack on maize. Though in some of the legume treatments, grain damage and grain losses were higher than in the maize alone plots, per area yields did not vary significantly.In southern Benin, the use of cover crops to improve and maintain soil fertility is on the increase. The present study investigated the effect of two leguminous cover crops, Canavalia ensiformis (L.) DC and Sesbania rostrata Brem. & Oberm., planted at different dates before maize (Zea mays (L.)), and cowpea (Vigna unguiculata L.) planted as border rows on infestations of maize by the pyralid Mussidia nigrivenella Ragonot and of other cob-boring lepidopteran pests. In both trials, M. nigrivenella densities at harvest tended to be higher in the maize alone than the legume treatments, but the effect depended on the timing of planting of the cover crop in relation to that of maize. There were no discernible trends for other borers such as the noctuid Sesamia calamistis Hampson, the pyralid Eldana saccharina Walker, and the tortricid Thaumatotibia leucotreta Meyrick. Furthermore, M. nigrivenella pest loads were considerably higher on C. ensiformis than maize, indicating that the presence of alternative host plant species in the vicinity of maize fields did not increase M. nigrivenella attack on maize. Though in some of the legume treatments, grain damage and grain losses were higher than in the maize alone plots, per area yields did not vary significantly.